Um framework para gerenciamento de qualidade de serviço em dispositivos móveis - Hobeika, Camillo Tannuri (Universidade Federal de São Carlos, 2004)
This work presents a Framework for Multimedia Applications with objective to make possible the use of these applications in Mobile Devices with limited computational capacity, considering the aspects of Quality of Service that can currently be used in these devices. The technological evolution cause a accented growth in the number of mobile device`s users, a time that the quality of the services also tends to increase, mainly as for the multimedia applications. Had to the characteristics of these devices and the nets where they operate, the traffic of multimedia information tends to increase the communication typical problems. However, parameters of Quality of Service (QoS) can be established and actions can be taken to try to diminish the impact of the inherent problems to the mobile computation in the multimedia applications. Thus, this work aims at the research and the development of one framework based on components for applications developed on the platform Java 2 Micro Edition (J2METM), of form to offer to greater quality in the multimedia communication for the mobile devices that possess limited resources.
Keywords: Sistemas multimídia; Framework (programa de computador); Java 2 micro edition; Aplicações multimídia; Qualidade de serviço; Sistemas de comunicação sem fio; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO